SISTEM INFORMASI E-LEARNING BERBASIS WEB SMP NEGERI 12 YOGYAKARTA - Setiyorini, Agustin; Ahmad, Rifzan (Universitas Janabadra, 2018)
With this computerized information system technology, it is expected to be able to bridge communication and interaction between students with teachers and vice versa. One use of computerized information systems in the school environment that is considered very appropriate for the problems above is the E-Learning Information System. The design of e-learning information system in the State Junior High School 12 Yogyakarta is intended to make it easier for students to manage materials and problems in a systematic and coherent manner, it is expected that manghandle tasks are systematized and structured, plays a role in setting student value, helping students to work on deadline this is related to discipline), facilitating communication between students and teachers and many other important benefits.From this research can be concluded that E-Learning Web Based Information System is a multifunctional information system that is able to help the process of learning and teaching in SMP Negeri 12 Yogyakarta which includes accessing the material, accessing news, giving feedback to the task and also the automatic assessment process. E-Learning Web Based Information System is also equipped with an online quiz that perfectly suits the needs of students in doing UAS and UAN which in fact has been based online interactivity. Keywords: system, informasi, e-learning, website, technology.